SECOND LANGUAGE ACQUISITION BASED ON GRAMMATICAL RULE FOR THE SECOND SEMESTER OF TADRIS BAHASA INGGRIS DEPARTMENT AT STAI MEMPAWAH - Dofir Dofir (International Journal of Teaching and Learning, 2023)
Language acquisition is very similar to the process students use in acquiring first and second languages. It requires meaningful interaction in the target language natural communication--in which speakers are concerned not with the form of their utterances but with the messages they are conveying and understanding. Error correction and explicit teaching of rules are not relevant to language acquisition (Brown, 1970), native speakers can modify their utterances addressed to acquirers to help them understand. Grammatical functions are assigned directly to the underlying representation in a more or less across the board fashion, only taking into consideration the language dependent semantic function hierarchy. This approach bypasses a number of constraints on subject assignment that may be gathered from data, and observed from the actual behaviour of speakers. We propose a treatment of Subject assignment on the basis of a combination of semantic factors of the relevant referents and other functional aspects of underlying representations. In Subject (and Object) assignment are now located in the daily diologue, in Mackenzie, J (2004).